Bayer prosesinde elde edilen vanadyum çamurlarından V205 üretimi - Sesigür, Hakan (Fen Bilimleri Enstitüsü, 1991)
Bu tez çalışmasında Etibank Seydişehir Alüminyum Tesis lerinden sağlanan vanadyum çamurlarından yüksek safiyette vanadyum pentaoksit üretiminin koşulları incelenmiştir. Bu amaçla üç grup deney yapılmıştır. Bunlar; - Çözümlendirme - Çözelti temizleme - Amonyum vanadat çöktürme deneyleridir. Çözümlendirme deneylerinde, çözümlendirme sıcaklığının ve katı/sıvı oranının etkisi incelenmiştir. Bu amaçla 60- 7D-8G ve 90 C'lerde çözümlendirme işlemleri yapılmıştır. Optimum çözümlendirme sıcaklığında ise katı/sıvı oranının etkisi incelenmiştir. Katı/sıvı oranının etüdünde 1/2.5- 1/5-1/10 oranları etüd edilmiştir. Çözelti temizleme deney lerinde teknik uygulamaya uygun olarak çözelti jips ile muamele edilmiş temizleme işlemi 95 C'de, pH=8-9'da ve sto- kiometrik CaSO, ihtiyacının 1.5 katı ile çalışılarak gerçek leştirilmiştir. Amonyum vanadat çöktürme deneylerinde çö zelti temizlemeden gelen vanadyum çözeltisinden pH 2. 5 'çj g yeterli miktarda amonyak ilavesi ile amonyum vanadat çöktü- rülmüştür. Çöktürme deneylerinde çözelti sıcaklığının çök türme verimine etkisi etüd edilmiştir. Bu tez kapsamında yapılan deneylerin sonucunda elde edilen önemli sonuçlar şu şekilde sıralanabilir. 1)- Optimum çözümlendirme şartalır, SO C, 1/5 katı/ sıvı aranı ve 2 saat çözümlendirme süresidir. Bu şartlar da yapılan deneylerde vanadyumu çözeltiye alma randımanı % 98'dir. 2)- Stokiometrik miktarın 1.5 katı CaSO, kullanılarak yapılan çözelti temizleme işlemi ile çözeltideki Al ile yarım saatte % 100 oranında temizlenmiştir. İki saatlik işlem sonucunda As % 38.7, P%kk oranında çözeltiden uzaklaş- tırılabilmektedir. 3)- l\IH, vanadat çöktürme işleminde, pH=2.5'a ayarlan dıktan sora stokiometrik miktarın 3 katı (hacimce % 5)amon- yak ilavesi ile oda sıcaklığında yapılan deneylerde çözel tideki vanadyumun % 92*si NH" -vanadat halinde çöktürüle- bilmiştir.

Vanadium takes place in the 4 group of the periodic table of the elements. Its atomic weight is 50.942 g/moles and its atomic number is 23. The dispersion of the vanadium reserves in the world is as follows. 6G % Soviet Union 20 % Republic of South Africa 14 % Republic of China 4 % USA Generaly, vanadium is used in industry in the forms of f errovanadium, V^O,- and metallic vanadium and have^ a wide operation field like; in the production of alloy steels 81 % vanadium is used in the form of ferro-vana- dium, in the production of vanadium alloys based on non-ferrous metals 3% vanadium is used in the form of U?0c as a catalysor. There are more than 65 vanadium minerals on the earth. The most common ones; VI Mineral Formula V2S +nS Patronite Bravoite Sulvanite Vanadinite Kornotite Titaniferrousmagnetite FeG.TiO?.FeO(Fe\y).G3 (Fe,Ni,U).S2 3Cu2S.\/2S5 pb5(UQ^)Cl KCa(UO^) (\yD^)3H2D Among these minerals only patronite has an economic value. In vanadium production from the other ores which don't contain enough vanadium to treatment are economicly, vanadium enriched by-products such as vanadium sludge, vanadium slag are used. In this study, vanadium sludge obtanied form Etibank Seydişehir Aluminium Company is used. The vana dium sludge capacity of the plant is 36D t/year and the 1/pO,- cantent is 11.20 %. The chemical composition of tne vanadium sludge obtained from the plant is given in Table 1. TABLE 1 : Chemical Composition of Vanadium Sludge Components % Moisture u2o5 P2D5 As203 Total Na A12D3 44.95 11.25 3.17 3.2 3.917 2Ü.54 2.73 To determine the optimal W?G,- manufacturing conditions from vanadium sludges which the chemical composition is given in Table 1, a group of experiments were done and the experimental procedure is given in Figure 1 as a flow sheet. Vll Uanadium sludge FIGURE : 1. The flowsheet of the experimental procedure. Vlll This study can be classified into 3 groups, (1 ) Leaching (2) Solution cleaning (3) NH, -vanadate roasting The effect of temperature and solid/liquid ratio on vanadium leaching yield are investigated in the leaching experiments. For this purpose, Qleaching experiments were carried out at 60 C, 70 C, BO C, and 90 C temperatures and at B0DC optimum leaching temperature is obtained. The effect of solid/liquid ratio at BO C is also investigated. For this purpose, experiments were performed at 1/2,5, 1/5, 1/10 solid/liquid rations and at 1/5 S/L ratio 9B % of vanadium is recovered in solution The results obtained from the leaching experiments are given in Table 2 and Table 3. TABLE: 2. Vanadium Concentrates Depending on Experimental Temperature and Duration (g/1) Time Room Temp. 60 70 B0 90 5 10 15 30 60 90 120 1440 TABLE: 3. Vanadium Concentrates Depending on the Leaching Temperature at different S/L Rations. Time 1/25 1/5 1/10 10. 1B 4.63 10.45 4.62 10.11 4.55 10.53 4.86 11.42 5.36 12.23 5.7B 12.40 6.46 IX In the solution cleaning which has tuo step, the solution is treated with jips. Impurity cleaning experiments are performed at 95 C pH=B-9 and % 50 excess of the stochiometric ratio. By this way, whale aluminium in the solution is cleaned in 30 minutes time, arsenic and P cleaning is 3B.7 % and 44 % respectively in 120 minutes time. The beheviours of \1, As, P and Al depending on duration during solution cleaning are give in Table 4a, 5b. TABLE: 4. a. Uanadium and Impurity Concentrations in Solution Cleaning (1st step) Time As Al 0 3G 60 90 120 2.43 TABLE: 4.b. Uanadium and Impurity Concentrations in nd Solution Cleaning ( 2 step) Time As 0 30 60 90 120 After the solution cleaning step, IMH, polivanadate precipitation from the cleaned solution experiments were carried out at pH=2.5 by NH~ addition. Here, NH, poli vanadate precipitation temperature was investigated. For this purpose a group of experiments were performed at room temperature, 3D C, 40 C and 50 C. The results obtanied from these group of experiments are given in Table 5.
V2O5 production from vanadium sludge of bayer process
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1991
Keywords: Vanadyum; Vanadyum pentoksit; Vanadyum çamuru; Vanadium; Vanadium pentoxide; Vanadium sludge